(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
A well-built banking sector is significant for aprosperous economy. The crash of the banking sector may have an unfavorableblow on other sectors. A banker shall be very cautious in lending, becausebanker is not lending money out of his own capital. A major portion of themoney lent comes from the deposits received from the public and governmentshare. At present NPA in the banking sector is debate topic because NPA isincreasing year by year particularly in nationalized banks The GrossNon-Performing Assets (GNPAs) of Nationalized Banks as on June 2012 wereRs.73,038 crore which amount to 2.94% of Gross Advances. In this directionpresent paper is undertaken to study the reasons for advances becoming NPA inthe Indian Commercial banks Sector and to give suitable suggestion to overcomethe mentioned problem. In India Non-performing assets are one of the majorconcerns for banks. NPA is the best indicator for the health of the bankingindustry. NPAs reflect the performances of banks. .NPAs is the primaryindicators of credit risk. NPAs are an inevitable burden on the bankingindustry. Hence the success of a bank depends upon methods of managing NPAs.The Public Sector Banks have shown very good performance over the privatesector banks as far as the financial operations are concerned.